Formation of Polyploid Giant Cancer Cells Involves in the Prognostic Value of Neoadjuvant Chemoradiation in Locally Advanced Rectal Cancer. (29th August 2019) - Fei, Fei; Zhang, Mingqing; Li, Bo; Zhao, Lizhong; Wang, Hui; Liu, Lina; Li, Yuwei; Ding, Po; Gu, Yanjun; Zhang, Xipeng; Jiang, Tao; Zhu, Siwei; et al.
Abstract : We previously reported that polyploid giant cancer cells (PGCCs) exhibit cancer stem cell properties and can generate daughter cells with the epithelial-mesenchymal transition phenotype. This study investigated the role of PGCC formation in the prognostic value of neoadjuvant chemoradiation therapy (nCRT) in locally advanced rectal cancer (LARC). The morphological characteristics were observed in patients with LARC after nCRT. Colorectal cancer cell lines were treated with irradiation or chemotherapeutic drugs, and the metastasis-related proteins were detected. 304 nCRT cases and 301 paired non-nCRT cases were collected for analysis. More PGCCs and morphologic characteristics related to invasion and metastasis appeared in tumor tissue after nCRT. Irradiation or chemicals could induce the formation of PGCCs with daughter cells exhibiting strong migratory, invasive, and proliferation abilities. In patients after nCRT, pathologic complete remission, partial remission, stable disease, and progressive disease were observed in 29 (9.54%), 125 (41.12%), 138 (45.39%), and 12 (3.95%) patients, respectively. Mucinous adenocarcinomas (MCs) occurred more frequently in nCRT than in non-nCRT patients ( χ 2  = 29.352, P = 0.001 ), and the prognosis in MC patients was worse than that in non-MC patients ( χ 2  = 24.617, P = 0.001 ). The difference in survival time had statistical significance for 60 days ( χ 2  = 5.357, P = 0.021 ) and 70 days ( χ 2  = 18.830, P = 0.001 ) rest interval time. On multivariable analysis, 60 days rest interval, Duke's stage, and recurrence and/or distant metastasis remained significant predictors of survival. In conclusion, irradiation or chemicals induce the formation of PGCCs and PGCCs produce daughter cells with strong migration and invasion abilities after a long incubation period. Appropriate rest interval (incubation period) is very important for patients with LARC who will receive nCRT.